2022
DOI: 10.1038/s41467-022-29386-2
|View full text |Cite|
|
Sign up to set email alerts
|

Northwestern Pacific tropical cyclone activity enhanced by increased Asian dust emissions during the Little Ice Age

Abstract: Instrumental records reveal that intense tropical cyclone (TC) activity varies with tropical sea surface temperature (SST) on annual-decadal scales. Drivers of intense TC activity at the centennial-millennial scale are less clear, due to the sparseness of pre-observational reconstructions. Here, we present a new 2 kyr continuous activity record of intense TCs from offshore eastern China. Our reconstruction indicates that this site witnessed enhanced TC activity during relatively warm periods, with a widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 80 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…In addition, we observe that the main phases of increased FC 32 1,15-diol proxy in core T06 coincide well with intervals of increased Asian dust emissions at 850-750 and 540-370 yr BP (Chen et al, 2020;Figures 4A, E). A marked increase in dust storm activity is related to an enhanced EAWM (Yang et al, 2022; Figures 4C, E). In conclusion, our study indicates that the EAWM and CDW are the main mechanisms controlling riverine OM input into the Yangtze River since the last 1000 years.…”
Section: Reconstructing the History Of Terrestrial Om Input Using The...mentioning
confidence: 90%
“…In addition, we observe that the main phases of increased FC 32 1,15-diol proxy in core T06 coincide well with intervals of increased Asian dust emissions at 850-750 and 540-370 yr BP (Chen et al, 2020;Figures 4A, E). A marked increase in dust storm activity is related to an enhanced EAWM (Yang et al, 2022; Figures 4C, E). In conclusion, our study indicates that the EAWM and CDW are the main mechanisms controlling riverine OM input into the Yangtze River since the last 1000 years.…”
Section: Reconstructing the History Of Terrestrial Om Input Using The...mentioning
confidence: 90%
“…3B, bottom). Previous studies revealed a suppressing effect of aerosols on TC activities over the Atlantic Basin (20,37) but an enhancing effect over the Pacific (38), both assuming linear relationships between aerosols and low-frequency SST variability over the multiyear and large spatial scale. Our ML model revealed a nonlinear relationship between the DOD and the TCR at the individual TC level, signifying the importance of examining the TC-SST-DOD interactions in a sophisticate analyzing framework.…”
Section: Nonmonotonic Relationship Between Dust and Tcrmentioning
confidence: 96%